2018
DOI: 10.1016/j.freeradbiomed.2018.03.045
|View full text |Cite
|
Sign up to set email alerts
|

A discrete role for alternative oxidase under hypoxia to increase nitric oxide and drive energy production

Abstract: Alternative oxidase (AOX) is an integral part of the mitochondrial electron transport and can prevent reactive oxygen species (ROS) and nitric oxide (NO) production under non-stressed, normoxic conditions. Here we assessed the roles of AOX by imposing stress under normoxia in comparison to hypoxic conditions using AOX over expressing (AOX OE) and anti-sense (AOX AS) transgenic Arabidopsis seedlings and roots. Under normoxic conditions stress was induced with the defence elicitor flagellin (flg22). AOX OE reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
75
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 41 publications
(51 reference statements)
6
75
0
1
Order By: Relevance
“…In contrast, the opposite results were obtained with the RNAi-aox strains. Previous studies with Arabidopsis thaliana have shown that under hypoxic stress, aox can regulate energy metabolism, affect ROS production and enhance resistance [61], and we obtained similar results. The formation of ROS is mainly due to the "single electron leakage" of respiratory chain components, and complexes I and III are considered the main sites of this electron leakage [62].…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, the opposite results were obtained with the RNAi-aox strains. Previous studies with Arabidopsis thaliana have shown that under hypoxic stress, aox can regulate energy metabolism, affect ROS production and enhance resistance [61], and we obtained similar results. The formation of ROS is mainly due to the "single electron leakage" of respiratory chain components, and complexes I and III are considered the main sites of this electron leakage [62].…”
Section: Discussionsupporting
confidence: 86%
“…Candidates include: nitric oxide (NO), shown to participate in stress signaling in plants (Delledonne et al ., ; Durner et al ., ; Neill et al ., ; de Pinto et al ., ) and to regulate AOX expression (Feng et al ., ), could serve as a signaling molecule. In A. thaliana , AOX overexpression led to NO increase, while AOX downregulation resulted in NO decrease (Vishwakarma et al ., ). NO accumulates in P. tricornutum cells treated with diatomā€derived aldehydes.…”
Section: Discussionmentioning
confidence: 97%
“…High concentrations of ascorbate in plant cells facilitates scavenging of superoxide (O2-) moreover, ascorbate peroxidase is also involved in H2O2 scavenging and reduction of NO2- to NO (Alegria et al, 2004). The ability of plants under hypoxia to synthesize ascorbate (Fig 8m) and induction of genes involved in the ascorbate-glutathione cycle (Fig 6) may be one of the reasons for production of reduced peroxynitrite under hypoxia (Vishwakarma et al ., 2018) despite of higher NO production by the mitochondrial COX and AOX (Gupta et al, 2005; Vishwakarma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%